Fact book Philippine financial system - Central Bank of the Philippines (Manila CBP, 1976)
Quarterly.
Table of Contents: The Philippine Banking System, A Regional Profile -- A. General Profile: 1. Banking Offices -- 2. Density Ratios -- 3. Selected Balance Sheet Accounts -- B. Individual Profile: Region I. Ilocos -- Region II. Cagayan Valley -- Region III. Central Luzon -- Region IV. Metro Manila -- Region IV-A. Southern Tagalog -- Region V. Bicol - Region VI. Western Visayas -- Region VII. Central Visayas -- Region VIII. Eastern Visayas -- Region IX. Western Mindanao -- Region X. Northern Mindanao -- Region XI. Southern Mindanao -- Region XII. Central Mindanao -- C. Appendix. Provincial Aggregates on Banking Offices and Selected Balance Sheet Accounts.
Keywords: Banks and banking -- Philippines; Financial institutions; Financial resources -- Philippines